1993
DOI: 10.1128/jcm.31.6.1450-1453.1993
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Helicobacter pylori infection by using pyloriset EIA-G and EIA-A for detection of serum immunoglobulin G (IgG) and IgA antibodies

Abstract: We evaluated the performance of new enzyme immunoassay (EIA) kits (Pyloriset; Orion Corporation, Orion Diagnostica, Espoo, Finland) for the detection of immunoglobulin G (IgG) and IgA antibodies to Helicobacter pylori in serum. Serum samples from 195 patients with upper abdominal complaints were collected. Biopsy specimens of the gastric mucosae were taken for histological analysis and bacterial culture. The sensitivity, specificity, positive and negative predictive values, and efficacy of the Pyloriset EIA-G … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 22 publications
(14 reference statements)
2
22
0
1
Order By: Relevance
“…Two ELISA kits detecting specific IgG were used and one kit detecting IgA. These kits have been found suitable for screening patients with H. pylori infection 16–18 and have already been used for patient follow‐up 19 ,. 20 The main advantage of the EPI kits (HM‐CAP and PP‐CAP) is their convenience, since the incubation times are shorter, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Two ELISA kits detecting specific IgG were used and one kit detecting IgA. These kits have been found suitable for screening patients with H. pylori infection 16–18 and have already been used for patient follow‐up 19 ,. 20 The main advantage of the EPI kits (HM‐CAP and PP‐CAP) is their convenience, since the incubation times are shorter, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…A range of ages was represented in the group, such that the population as a whole was not composed primarily of older individuals, in whom a higher incidence of H. pylori infection and atrophic gastritis might be expected. It has been suggested that the presence of atrophic gastritis may result in a positive serology (as an indicator of ''inactive'' or past infection) with a negative biopsy or UBT result (9,13). Although the mean age of the UBT-positive group was slightly higher than the mean age of the UBT-negative group, the mean age of the group demonstrating false-positive G.A.P.…”
Section: Discussionmentioning
confidence: 99%
“…A serological assay for H. pylori IgG antibodies was performed using an enzyme-linked immunosorbent assay (ELISA) (Pyloriset EIA-G kit, Orion Diagnostica, Espoo, Finland). 19 A positive result was defined as a titer of antibodies of 20 IU/mL or greater, according to the manufacturer's recommendations. The HELICO BLOT 2.1 (Genelabs Diagnostics, Singapore Science Park) was used for the detection of antibodies to specific proteins of H. pylori, including pathogenic factors (e.g., CagA), as previously described.…”
Section: H Pylori Infection Diagnosismentioning
confidence: 99%